INTERNALISASI STIGMA & HARGA DIRI PADA ORANG DENGAN SKIZOFRENIA - Indri Jayanti; Fellianti Muzdalifah (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2013)
The aim of this study is to analyze the influence internalized stigma on self-esteem in people with schizophrenia (outpatients) in Jakarta. The research was held in Komunitas Peduli Skizofrenia Indonesia, Puskesmas Tebet, and Klender Islamic Mental Hospital on November 2012. This research used quantitative ex-post facto research method. This research used incidental sampling. Collecting data used scale of internalization stigma which is adapted from ISMI (Internalization Stigma of Mental Illness) scale and self-esteem scale’s Rosenberg, were assessed among 42 outpatients who have schizophrenia. Statistical analysis obtainded using the Regression test. Based on the result of data analysis found that adjusted R square internalized stigma on self-esteem was 0,176 (17,6%), which means that influence internalized stigma to self-esteem was 17,6% and 82,4% influenced by others factors beyond self-esteem. This result showed that fluctuation of self-esteem in people with schizophrenia (outpatients) contrary to fluctuation of internalized stigma variable.